DOES THE GENDER GAP IN DELINQUENCY VARY BY LEVEL OF PATRIARCHY? A CROSS‐NATIONAL COMPARATIVE ANALYSIS1. Issue 4 (4th November 2017) - SAVOLAINEN, JUKKA; APPLIN, SAMANTHA; MESSNER, STEVEN F.; HUGHES, LORINE A.; LYTLE, ROBERT; KIVIVUORI, JANNE
Abstract: We examined cross‐national variation in the gender differential in offending, which is often referred to as the gender gap in crime. Analyses were directed toward two empirical questions: 1) Is the gender gap narrower in less patriarchal sociocultural settings, and if so, 2) is this outcome a result of higher levels of offending on the part of girls, lower levels of offending on the part of boys, or some combination thereof? To address these questions, we compiled a multilevel, cross‐national data set combining information on self‐reported offending from the second International Self Report Delinquency Survey (ISRD‐2) with normative and structural indicators of societal levels of patriarchy. The results from regression equations showed the gender gap in delinquency to be narrower at reduced national levels of patriarchy. The predicted probabilities calculated from regression coefficients suggested that this narrowing is a result of increased offending among girls and, to some extent, of decreased offending among boys in less patriarchal nations. Sensitivity checks with alternative model specifications confirmed these patterns but also identified a potential outlier. We discuss the implications of these descriptive findings for etiological research and theory.